(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The Kabuyutan Ciburuy site is a cultural heritage that is still unknown, let alone widely known. A few residents, especially students, haven’t learned or gone to that place. Thus it is necessary to introduce and promote efforts, to maintain the existence of cultural heritage because when it is forgotten, the historical evidence will slowly disappear. The purpose of holding this community service is to improve and introduce digital promotional media that can be used as a medium in promoting Cultural Heritage in Pamalayan Village, Bayongbong District, Garut Regency. The method used in this service is to provide assistance and training. The training is carried out for seven days by providing material and direct practice related to photography, videography, writing blogs, and managing social media. Some things that can motivate residents, especially students, in promoting cultural heritage include: (1). Creating websites and social media accounts for promotional sites; (2). Provide an understanding of the potential of the Ciburuy Kabuyutan Site; (3). Forming a culture-based community to maintain consistency in efforts to promote cultural heritage. The result of this activity is the awakened understanding of the audience about the digital world, especially in the digital promotion process, marked by an increase in the percentage of post-test results, from 41% to 85%. Several partners have also been able to independently create written works that have been published on the website and also social media from the Ciburuy site that has been made. As well as the establishment of a culture-based community called the Sadaya Community.